Biocrude oil production via hydrothermal liquefaction of food waste in a simplified high-throughput reactor. (December 2021) - Saengsuriwong, Ruetai; Onsree, Thossaporn; Phromphithak, Sanphawat; Tippayawong, Nakorn
Graphical abstract: Highlights: Organic biocrude oil generated from hydrothermal processing of food waste. Over 55% total liquid yields obtained, about 73% of which was biocrude. GCxGC/TOF-MS used in chemical analysis of organic biocrude and aqueous products. Abstract: In this study, the hydrothermal liquefaction of food waste was investigated for generating bio-oils or biocrudes using a simplified high-throughput reactor. Different operating conditions were parametrically tested for obtaining maximum yield of biocrudes at temperatures from 280 to 340 °C and sample-to-water mixture ratios from 1:3 to 1:7, with 30 min residence time. The biocrude yields were found to increase significantly with increasing temperature and mixture ratio. A maximum biocrude yield of approximately 40% w/w dry basis (from a total liquid product yield of over 56% w/w) and energy recovery of over 70% were obtained at 340 °C and a mixture ratio of 1:7. High heating values of the resulting biocrude and solid residue were remarkably better than those of the raw material. Fatty acids, amides, N-containing compounds, and cyclic ketones were identified to be the main components of the biocrudes using advanced GCxGC/TOF-MS.